Urban forms : death and life of the urban block - Panerai, Philippe (Architectural Press, 2004)
This popular and influential work, translated here into English for the first time, argues that modern urbanism has upset the morphology of cities, abolished their streets and isolated their buildings. In tracing the stages of this transformation, this book presents the view that the urban tissue, the intermediate scale between the architecture of buildings and the diagrammatic layouts of town planning, is the essential framework for everyday life. Only by investigating the urban tissue will it be possible to understand the complex relationships between plot and built form, between streets and.